2021
DOI: 10.3390/jof7121030
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid Regulates the Colonization and Dissemination of Candida albicans from the Gastrointestinal Tract by Controlling Host Defense System and Microbiota

Abstract: Candida albicans (CA), a commensal and opportunistic eukaryotic organism, frequently inhabits the gastrointestinal (GI) tract and causes life-threatening infections. Antibiotic-induced gut dysbiosis is a major risk factor for increased CA colonization and dissemination from the GI tract. We identified a significant increase of taurocholic acid (TCA), a major bile acid in antibiotic-treated mice susceptible to CA infection. In vivo findings indicate that administration of TCA through drinking water is sufficien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 117 publications
(139 reference statements)
3
20
0
Order By: Relevance
“…Dysregulation in host immunity and (or) gut microbiota dysbiosis are the major predisposing factors that contribute to increased CA colonization and (or) dissemination from the intestine [ 6 , 7 , 8 , 9 , 10 ]. Therefore, understanding the factors that regulate CA colonization and dissemination will lead to the identification of novel approaches to prevent and treat life-threatening fungal infections in humans [ 11 , 12 , 13 , 14 ]. To address this gap in the knowledge, we utilize a combination of targeted metabolomics, 16S ribosomal RNA amplicon gene sequencing, and in-vivo mouse models of CA infection to identify the metabolites, microbiome, and host factors regulating CA colonization in the intestine [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dysregulation in host immunity and (or) gut microbiota dysbiosis are the major predisposing factors that contribute to increased CA colonization and (or) dissemination from the intestine [ 6 , 7 , 8 , 9 , 10 ]. Therefore, understanding the factors that regulate CA colonization and dissemination will lead to the identification of novel approaches to prevent and treat life-threatening fungal infections in humans [ 11 , 12 , 13 , 14 ]. To address this gap in the knowledge, we utilize a combination of targeted metabolomics, 16S ribosomal RNA amplicon gene sequencing, and in-vivo mouse models of CA infection to identify the metabolites, microbiome, and host factors regulating CA colonization in the intestine [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous findings indicate that taurocholic acid ( TCA ), a major bile acid present in both humans and mice, controls the balance between commensalism and invasive CA infection originating from the gut [ 14 ]. Oral administration of TCA through drinking water is sufficient to induce CA colonization and dissemination from the intestine, even in the absence of antibiotic and (or) immunosuppressive treatment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, upon antibiotic treatment, which causes dysbiosis of the gastrointestinal tract, a disruption in the commensal relationship between the host and fungal pathogen, Candida albicans , can be observed. One effect is a significant increase in the production of a major bile acid (i.e., taurocholic acid,) which enhances susceptibility of mice to C. albicans infection by inducing colonization and dissemination of the fungi throughout the host [ 10 ]. The study also showed a change in the commensal bacterial population within the gastrointestinal tract of the host upon taurocholic acid treatment, which supports the regulatory role commensal bacteria play in promoting host homeostasis in the presence of fungal pathogens.…”
mentioning
confidence: 99%